Mn(II) and Zn(II) ions catalytic oxidation of o-phenylenediamine and characterization, X-ray crystal structure and solution study of the final products DAPH+Cl−·3H2O and [DAPH][Zn(dipicH)(dipic)]·4H2O. (28th May 2016) - Ghasemi, Khaled; Ghasemi, Fatemeh; Rezvani, Ali Reza; Shokrollahi, Ardeshir; Refahi, Masoud; García-Granda, Santiago; Mendoza-Meroño, Rafael
Graphical abstract: The reactions between o-phenylenediamine and dipicH2 with Mn(II) and Zn(II) ions were investigated and the resulting products characterized by some spectroscopic methods. In the reaction process two molecules of o-phenylenediamine have reacted and produced 2, 3-diaminophenanzineum. Solution potentiometric studies were also compared with the solid-state results. Abstract: Compound DAPH + Cl − ·3H2 O (1 ), and complexes Mn(dipic)(H2 O)3 (2 ) and [DAPH][Zn(dipicH)(dipic)]·4H2 O (3 ), (dipicH2 = 2, 6-pyridinedicarboxylic acid and DAP = 2, 3-diaminophenazine) were prepared from the reaction of MgCl2 ·4H2 O and ZnCl2 with mixture of o-phenylenediamine (OPD) and 2, 6-pyridinedicarboxylic acid in water. These compounds were characterized by elemental analysis, FTIR, 1 H NMR and UV–Vis spectroscopy. The solid-state structure of [DAPH][Zn(dipicH)(dipic)]·4H2 O (monoclinic, P21 /c) was determined by the single crystal X-ray diffraction method. The protonation constants of dipic and DAP, in all of probability protonated forms, the equilibrium constants for the dipic–DAP proton transfer system and the stoichiometry and stability constants of binary and ternary complexes of this system with Zn 2+ and Mn 2+ ions in aqueous solution were investigated by the potentiometric pH titration method. The stoichiometries of the most complex species in solution were compared with corresponding crystalline complexes in the solid state.